Sistem Informasi Pemesanan Baju Olahraga Berbasis Web Pada Konveksi “Adher” Tammerodo Sendana Majene - Maspiati; Nasruddin; Musliadi KH (Scientific Literacy Innovation and Technology Journal, 2024)
The very rapid development of technology is currently bringing us into the era of modernization, almost all aspects of human life are very dependent on technology, this is because technology was created to help and make it easier for humans to complete an activity or job. The impact of technological developments on daily life and aims to optimize sportswear sales services through a web-based application,